Gambaran Kebiasaan Merokok dan Paparan Rokok pada Remaja di Indonesia - Dea Rosalina Ritonga; Khairunsyah Khairunsyah; Nadia Syahputri Sinaga; Muhammad Rafly; Raisya Rhadella Br Ginting; Wahyudi Wahyudi (Pusat Riset dan Inovasi Nasional, 2025)
Smoking is one of the most common behaviors among adolescents, especially in Indonesia. This habit not only impacts on individual health, but also has far-reaching social and economic consequences. Smoking is a national problem that is difficult to solve where this activity is still often carried out by many people. Although it is often written in newspapers, magazines and the mass world stating the dangers of smoking, in fact some people still smoke frequently. According to data from the Ministry of Health, the prevalence of smoking among Indonesian adolescents has shown an alarming increase in recent years. In terms of health smoking should be stopped, because it can cause lung cancer and blockage of blood vessels that can cause death. Cigarettes consist of more than 4000 chemicals of which one of the main elements is nicotine. Nicotine can increase adrenaline secretion in the adrenal cortex which promotes an increase in serum acid concentration. The smoke produced from plants Nicotiana tobacum, Nicotiana rustica and other species or synthetics whose smoke contains nicotine which is addictive and not carcinogenic.addiction as a disease of free will. Where smoking is a voluntary behavior that makes a person feel addicted. But with the dangers of smoking that have been mentioned until now there are no policies and regulations governing age limits for cigarette buyers in Indonesia which causes elementary school children to be free to buy cigarettes at outlets or in stores.